Ginsenoside Rb1 affects mitochondrial Ca2+ transport and inhibits fat deposition and fibrosis by regulating the wnt signaling pathway to treat rotator cuff tears via docking with SFRP1 - Yuesong Yin; Hai Hu; Yian Yang; Song Wu (Molecular Medicine)
Abstract Background Rotator cuff tears (RCTs) are among the most common musculoskeletal disorders that affect quality of life. This study aimed to investigate the efficacy of ginsenoside Rb1 in RCTs and the mechanisms involved. Methods First, a fibrotic model of FAPs was induced, and FAPs were cultured in media supplemented with different concentrations of ginsenoside Rb1. Next, a rat model of RCTs was constructed and treated with ginsenoside Rb1. Molecular docking was subsequently utilized to detect the binding of ginsenoside Rb1 and SFRP1. Finally, SFRP1 was knocked down and overexpressed in vivo and in vitro to investigate the mechanism of ginsenoside Rb1 and SFRP1 in RCTs. Results Compared with the Normal group, FAP viability was decreased, but Collagen II, FN and α-SMA levels were increased in the Control group. After treatment with different concentrations of ginsenoside Rb1, FAP viability increased, but Collagen II, FN and α-SMA levels decreased. Among them, 60 µM ginsenoside Rb1 had the best effect. In vivo experiments revealed that ginsenoside Rb1 improved RCTs in rats. Molecular docking revealed the binding of ginsenoside Rb1 to SFRP1. Additionally, SFRP1 levels were lower in the Control group than in the Normal group. After treatment with ginsenoside Rb1, SFRP1 levels increased. In vivo, overexpressing SFRP1 along with ginsenoside Rb1 treatment further alleviated tendon tissue fibroblast infiltration and fat accumulation and further reduced the expression of Collagen II, FN, and α-SMA. In vitro, overexpressing SFRP1 along with ginsenoside Rb1 treatment further decreased the expression of CaMKII, PLC, PKC, Wnt, and β-catenin, further decreased the Ca2+ fluorescence intensity and mitochondrial length, increased the red/green intensity, and decreased the MitoSOX fluorescence intensity. Additionally, overexpressing SFRP1 along with ginsenoside Rb1 treatment further increased cell proliferation, decreased apoptosis, reduced the protein expression of Collagen II, FN, and α-SMA in muscle tissue, and further reduced the levels of TNF-α, IL-1β, and IL-6 in the cell supernatant. Conclusions Ginsenoside Rb1 inhibited the activation of the Wnt signaling pathway by promoting SFRP1 expression, thereby inhibiting mitochondrial function and Ca2+ absorption to treat fat infiltration and muscle fibrosis caused by RCTs.